Impact of the Make Healthy Normal mass media campaign (Phase 1) on knowledge, attitudes and behaviours: a cohort study. (12th April 2018) - Kite, James; Gale, Joanne; Grunseit, Anne; Bellew, William; Li, Vincy; Lloyd, Beverley; Maxwell, Michelle; Vineburg, John; Bauman, Adrian
Abstract: Objective : To determine the impact of the first phase of the Make Healthy Normal mass media campaign on NSW adults' active living and healthy eating knowledge, attitudes, intentions and behaviour. Methods : Cohort design with NSW adults, followed up three times over 12 months, with n=939 participants completing all three waves. We used generalised linear mixed models to examine campaign awareness, knowledge, attitudes, intentions and behaviours over time. Results : Campaign recognition built to a reasonable level (45% at Wave 3), although unprompted recall was low (9% at Wave 3). There were significant increases in knowledge of physical activity recommendations (46% to 50%), the health effects of obesity (52% to 64%), and weight loss benefits (53% to 65%), with stronger effects in campaign recognisers. Conversely, we found declines in self‐efficacy and intention to increase physical activity (39% to 31%) and decrease soft drink consumption (31% to 24%). Conclusions : Overall, there are some positives for the campaign but intentions need to be a focus of future campaign phases. Continued investment over the medium‐ to long‐term is needed. Implications : Mass media campaigns can play a role in obesity prevention but robust evaluations are needed to identify the characteristics of effective campaigns.